PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS NEARPOD UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI KELAS X SMA NEGERI 1 MEDAN - Melvany Agustini Sinurat; Arwansyah Arwansyah (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Economics learning in high school is still dominated by lecture methods and the use of less interactive media, resulting in low student engagement and learning outcomes. This study aims to develop interactive Nearpod-based learning media on Banking, Non-Bank Financial Industry, and Capital Market materials, and to test its feasibility and effectiveness in improving the learning outcomes of grade X students of SMA Negeri 1 Medan. This study uses the Research and Development (R&D) method with the ADDIE development model which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The research subjects consisted of validators including material experts, media experts, and learning design experts, as well as grade X students of SMA Negeri 1 Medan. Data collection techniques were carried out through observation, questionnaires, documentation, and learning outcome tests. Data analysis used quantitative descriptive analysis, Independent Sample t-test, and Normalized Gain (N-Gain). The results showed that Nearpod-based learning media obtained a feasibility percentage of 88% based on media expert assessments and student responses of 93% with a very feasible category. The effectiveness test results showed a significant difference in learning outcomes between the experimental and control classes (Sig. = 0.000 < 0.05). The N-Gain value of the experimental class was 0.763, which is in the high category, while the control class was 0.565, which is in the medium category. Thus, the Nearpod-based interactive learning media was declared feasible and effective in improving student learning outcomes in Economics.